Surgical treatment for mediastinitis after endobronchial ultrasound-guided transbronchial needle aspiration: 2 case reports. (2020) - Han, Sung Joon; Chong, Yooyoung; Shim, Man-shik; Han, Woosik; Cho, Hyun Jin; Kang, Shin Kwang; Yu, Jae Hyeon
Highlights: Mediastinitis by endobronchial ultrasound-guided transbronchial needle aspiration. EBUS-related mediastinitis is treated effectively by surgical drainage. Combination of surgery and medical treatment can be very effective in the treatment of inflammation caused by EBUS. Abstract: We report two cases of severe mediastinitis accompanied by abscess due to endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA), that were successfully treated by effective surgical drainage. A 68-year-old woman was referred to our hospital due to chest discomfort and high fever after EBUS-TBNA, and a 54-year-old man was referred due to general weakness, chills, and high fever after the same procedure. Both were diagnosed with EBUS-related mediastinitis and discharged after surgical treatment. Similar to previous reports, the importance of surgical procedures for mediastinitis caused by EBUS-TBNA was suggested. Further research and establishment of guidelines on this matter is necessary.